Optimization of Legal Education for Drugs Abuse Prevention in Tegalrejo District Yogyakarta - Ramadhan, Muhammad; Ariyanti, Dwi Oktafia; Arifin, Ridwan (Universitas Negeri Semarang, 2020)
Drug abuse as an extraordinary crime is carried out by involving many countries and a very large network, including Indonesia and especially in the province of D.I. Yogyakarta, known as a student city. However, the predicate city of students cannot make the province of D.I. Yogyakarta free from the dangers of drugs, instead it is ranked as the first province in Indonesia with the most users. Thus the need for education and understanding provided to the community, especially in the Tegalrejo sub-district region, is expected to reduce the number of drug users. The educational activities carried out received enthusiasm from the residents of Tegalrejo, which was attended by many residents from various backgrounds, starting from community leaders, village officials and attended by local youth or youth. From legal education activities to the dangers of drugs, participants who participate in these activities can understand all kinds of forms and types of drugs, apart from that, they also get knowledge of the effects of the dangers of drugs and can find out the characteristics of users to be more aware of in social relations with others. The advice given is to collect suspicious migrant data and strengthen positive activities from village officials and youth organizations so that Tegalrejo sub-district is free from drug threats.